2^12x3^5-4^6x9^2
(2^2x3)^ 6 + 8^4 x 3^5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
tính vế trên trước: 2^12 x 3^5 - 4^6 x 9^2 = 4096 x 243 - 4096 x 81 = 4096 x ( 243 - 81 ) = 663552.
tính vế dưới sau : ( 2^2 x 3 )^6 + 8^4 x 3^5 = ( 4 x 3 )^6 + 4096 x 243 = 12^6 + 995328 = 2985984 + 995328 = 3981312.
Vậy được: 663552/3981312 = 1/6.
1: Sửa đề: 3x-5
\(=\dfrac{-x^2\left(3x-5\right)-3\left(3x-5\right)}{3x-5}=-x^2-3\)
2: \(=\dfrac{5x^4-5x^3+14x^3-14x^2+12x^2-12x+8x-8}{x-1}\)
=5x^2+14x^2+12x+8
3: \(=\dfrac{5x^3+10x^2+4x^2+8x+4x+8}{x+2}=5x^2+4x+4\)
4: \(=\dfrac{\left(x^2-1\right)\left(x^2+1\right)-2x\left(x^2-1\right)}{x^2-1}=x^2+1-2x\)
5: \(=\dfrac{x^2\left(5-3x\right)+3\left(5-3x\right)}{5-3x}=x^2+3\)